Pengembangan Proses Belajar Mengajar Melalui Pelatihan Komunikasi Efektif Guru Yayasan Pendidikan Islam Al-Badi Nurul Huda, Sunter, Jakarta Utara - Davis Roganda Parlindungan; Salman naning (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
Teachers' effective communication skills are critical in conveying knowledge and skills to students in the classroom during the learning process. It is intended that students be encouraged to be involved and motivated in the learning process so that understanding can be built between teachers and students in order to achieve the teaching and learning process's objectives. Effective communication in interpersonal relationships between teachers and students during the teaching and learning process that includes elements of understanding can create a sense of pleasure, influence attitudes, and improve social relationships, all of which eventually lead to interactive actions for each other. As a result, training in effective communication techniques for teachers in the teaching and learning environments is essential.